(untitled) (Applied Biological Research, 2023)
The present study was conducted to standardize the efficient and reliable surface sterilization and callus induction protocol for 22 rice (Oryza sativa L.) varieties developed by Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli, Maharashtra (India) using different combinations of various plant growth regulators. The dehusked mature rice seed was used as explant. Prior to callus induction, surface sterilization protocol was standardized using 70% ethanol and different concentrations of mercuric chloride (HgCl2). The results revealed that surface sterilization treatment with 70% ethanol for 1 min, followed by 1.0% HgCl2 for 10 min and then washing the seeds 4-5 times was most effective in establishing maximum aseptic cultures (86.67%). Callus induction potential differed significantly among the rice varieties for the concentrations of plant growth regulators in MS medium. Rice cv. ‘Ratnagiri-711’ followed by cv. ‘Karjat-8’ were most superior in callus induction and proliferation potential with the respective callus induction frequency of 87.56 and 87.0%, and callus weight of 269.37 and 235.20 mg after 45 days of inoculation. The supplementation of 2,4-D @ 1.0 to 2.0 mg L-1 along with 0.5 mg L-1 BAP in MS medium was found optimum for embryogenic callus formation. All the calli formed on MS medium supplemented with combinations of plant growth regulators were yellowish-white in colour but with different textures as compact, soft, friable that were embryogenic and mucilaginous that were non embryogenic.